Structural hybridization and economical optimization of strengthening systems used for concrete beams / Md. Moshiur Rahman - Md. Moshiur, Rahman (2016)
Strengthening of an existing structure is often necessary to increase its load carrying capacity to meet new strength and serviceability requirements. However, strengthening can lead premature failure and efficient usage of the strengthening materials should be emphasized. Therefore, an efficient strengthening method along with the preparation of relevant design guidelines is urgently required. To address this issue a combination of external bonding reinforcement (EBR) and Near Surface Mounting (NSM) technique was developed and tested in this study. The proposed technique is called the hybrid strengthening method (HSM). In this study, efficient approach of strengthening reinforced concrete beam were also studied along with introduction of HSM. To prevent premature failure the use of end anchorage, shear strengthening and side HSM were employed. In order to make strengthening method efficient, steel bar with cement mortar was also used to replace the fibre reinforced polymer (FRP) and epoxy. Semi-numerical and finite element models were developed and validated with the experimental results to be used in the preparation of design guidelines. To help the designer reduce the strengthening cost further, mathematical design optimization techniques are also presented. For this study, thirty-three reinforced concrete beams were cast and tested. These were designed to address the objectives described above. The strengthening materials used comprised of steel bars, steel plates and CFRP composites with different dimensions were used for strengthening. The beams were extensively instrumented to monitor loads, deflections, and strains. The beams were subjected to static and fatigue loadings. Semi-numerical models were formulated to initiate the preparation of the design procedure of the HSM beam. In these models, an analytical approach was made with the help of the genetic algorithm optimization procedure to avoid time-consuming trial and error. In addition, finite element models (FEM) from the ABAQUS package to predict flexural strength and deflection were used to do the parametric study. In the mathematical design optimization method, the strengthening cost was minimized using non-linear programming and genetic algorithms where flexural strength and serviceability requirements were used as the major constraints. From the experimental results, the HSM beam, in general, gave about 65% higher flexural capacities as compared to the control beam at best. In terms of the efficiency, the HSM beams showed a 36% increase in flexural capacities as compared to the EBR beam. The partial replacement of epoxy adhesive with cement mortar in NSM strengthening reduced costs without significantly affecting the flexure performance. The fatigue performance of the HSM strengthened beam was found to be at least 6.5% higher than that of the NSM strengthened beam. The semi-numerical and finite element models were shown to be able to give consistent results as compared to the experimental results. The application of the optimization method led to savings of up to 8% in the amount of strengthening materials used as compared to classical design solutions.